Comparison of Different Mulching Materials in Teak Nursery Bed - Sudhakara, K. (Indian Forester, 2013)
Nine mulching materials were tested in addition to a control, viz., polythene sheets of different colours namely, transparent, blue, red, black, and white, single layer of newspaper, paddy straw, Eupatorium and gunny bag. After one year, two additional polythene sheets were tested viz., yellow and green, but white polythene sheet was not available. Combined results of both years showedthat newspaper mulch gave the largest germination percent of 50.38 (pâ‰¤ 0.000) which was 28% more than the control. This was followed by paddy straw, Eupatorium and gunny bag mulches in the decreasing order, though the differences were not significant. Mulching with green (lowest germination percentage of 22.75), yellow and blue polythene sheets gave significantly less germination percentage compared to the control. Transparent and white polythene were at par with the control. More or less similar results were obtained with regard to vigour parameters (pâ‰¤ 0.000).